Formulation and Evaluation of Aloe barbadensis Miller Mucilage Based Controlled Release Matrix Tablets of Glimepiride - Abdul Ahad, Hindustan; Sreeramulu, J.; Hima Bindu, V.; Padmanabha Reddy, Y. (Asian Journal of Chemistry, 2010)
This work aims to investigate and formulating controlled release matrix tablets of glimepiride with the mucilage from the leaves of Aloe barbadensis Miller and to study its functionality as an excipient in pharmaceutical controlled-release tablet formulations. The mucilage was extracted from Aloe barbadensis Miller leaves and physico-chemical properties of dried powdered mucilage were studied. Various formulations of glimepiride with Aloe barbadensis mucilage F1, F2, F3, F4 and F5 (1:0.8, 1:1.6, 1:2.4, 1:3.2, and 1:4, respectively) were prepared. These matrix tablets were evaluated for their physical properties like general appearance, thickness, hardness, friability, weight variation and uniformity of drug content, as per IP method. All the prepared matrix tablets were found to have good physico-chemical properties with low SD values. The swelling behaviour and release rate characteristics of the formulations were studied. The rate of release was faster in batch F1 and slower in batch F5. The result showed that as the proportion of mucilage increased, the overall time of release of the drug from the matrix tablet increased The dissolution study proved that the dried mucilage of Aloe barbadensis miller can be used as an excipient for making controlled release tablets.